The Polish World and the German World in Marian’s Turwid Novel Dwie Strony Drogi and in Gerard Górnicki’s works - Tauer, Sebastian (Contrasts in humanities: literature, language, culture, 2023)
This article shows the contrasts that can be noticed when analyzing the novel Dwie strony drogi by Marian Turwid. The author focuses on the contrasts both inside and outside the work. Differences in the presentation of the Polish and German world by Turwid are discussed, how they change during the novel’s action, and the differences that occur in such representations between Turwid’s work and other works in which the creation is shown. The place of this novel in a landscape of the communist period, stating that it is an extraordinary work in terms of the ideological message, which is to show Polish-German relations as a coexistence.